Surgical Resection of Primary Tumors Provides Survival Benefits for Lung Cancer Patients With Unexpected Pleural Dissemination - Fan, Liwen; Yang, Haitang; Han, Ke; Zhao, Yang; Gao, Wen; Schmid, Ralph A.; Yao, Feng; Zhao, Heng (Frontiers in Surgery, 2021)
Background: Surgery is not generally recommended for non-small cell lung cancer (NSCLC) patients with malignant pleural dissemination (PD). However, in some cases, PD is found unexpectedly during surgery. There is no consensus on whether surgical intervention can provide survival benefit for them. We investigated the role of surgery in NSCLC patients with unexpected PD by a cohort study. Methods: Clinical data of consecutive patients who intended to undergo radical surgery for NSCLC between January 2010 and December 2015 at Shanghai Chest Hospital and Huadong Hospital were collected from a lung cancer database. Patients diagnosed with unexpected malignant pleural nodules intraoperatively were enrolled in this retrospective study. Results: A total of 181 NSCLC patients were diagnosed with unexpected malignant PD intraoperatively and confirmed with postoperatively histological examinations. Out of these, 80 (44.2%) patients received pleural nodule biopsies alone, and 101 (55.8%) received primary tumor resection (47 with sublobar resection and 54 with lobectomy). The median progression-free survival and overall survival for all patients were 13 and 41 months respectively. Patients in the resection group had significantly better progression-free survival (19.0 vs. 10.0 months, P < 0.0001) and overall survival (48.0 vs. 33.0 months, P < 0.0001) than patients in the biopsy group. In the resection group, there was no statistical difference between patients with sublobar resection and lobectomy (P = 0.34). Univariate and multivariate analyses identified primary tumor resection, targeted adjuvant therapy, and tumor size (≤ 3 cm) as independent prognostic factors. Conclusions: NSCLC patients with unexpected intraoperative PD potentially benefited from surgical resection of the primary tumor and multidisciplinary targeted therapy, particularly when tumor size did not exceed 3 cm. Our data demonstrated that the resection type was not associated with survival differences, which remains to be defined with a larger sample size.